Trend Rooftop Restaurant And Bar Sebagai Daya Tarik Wisata Kuliner di DKI Jakarta - Larini, Cindy; Suryawan, Ida Bagus (JURNAL DESTINASI PARIWISATA, 2019)
In the middle of the city is really hard to find a touri st attraction based on nature because usually the city is full of buildings. However, it is not impossible to build a touri st attraction in a city. Nowadays, there are many buildings that being used as touris t attraction based on rooftop restaurant and bar. This phenomenon is not only happened in Indonesia, but also becoming urban tourism trend in theworld. The data for this observation is collected by doing an observation, in-depth interview with the informants, and researching on archive collection s about rooftop restaurant and bar. The informants were determined based on purposive sampling, where the informants were selected based on certain specification. The informants of this observation are The Cloud Lounge & Dining Jakarta ’s manager, SKYE Bar & Restaurant ’s manager,  and Henshin ’s supervisor. The result of this observation are touris t attraction in those rooftop restaurant s and bar s , and the development on each of the rooftop restaurant s and bar s every years. The development on rooftop restaurant and bar were analyzed by using fishbone analysis to see the impact of the changes on each rooftop restaurant s and bar s .   Key words : Urban Tourism, TouristAttraction, Rooftop Restaurant andBar, Fishbone Analysis.